2022
DOI: 10.1136/bmjopen-2021-060480
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and long-term health outcomes following myocardial infarction: protocol for a multicentre, prospective cohort study (ENHEARTEN study)

Abstract: IntroductionLow health literacy is common in people with cardiovascular disease and may be one factor that affects an individual’s ability to maintain secondary prevention health behaviours following myocardial infarction (MI). However, little is known about the association between health literacy and longer-term health outcomes in people with MI. The ENhancing HEAlth literacy in secondary pRevenTion of cardiac evENts (ENHEARTEN) study aims to examine the relationship between health literacy and a number of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Evidence also shows that these populations receive suboptimal healthcare access compared to other population groups 64 . Healthcare services have an important role to play in addressing this social gradient, 65 by ensuring that the care they provide is accessible for all, including culturally and linguistically diverse communities, minority groups and those with lower socioeconomic status 66 . Use of the co‐design approach can take context‐specific challenges of ‘underserved’ population groups into consideration to provide a culturally appropriate and logistically sound CVD intervention that is feasible and acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also shows that these populations receive suboptimal healthcare access compared to other population groups 64 . Healthcare services have an important role to play in addressing this social gradient, 65 by ensuring that the care they provide is accessible for all, including culturally and linguistically diverse communities, minority groups and those with lower socioeconomic status 66 . Use of the co‐design approach can take context‐specific challenges of ‘underserved’ population groups into consideration to provide a culturally appropriate and logistically sound CVD intervention that is feasible and acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Health Literacy Questionnaire (HLQ) covers nine different domains of health literacy and therefore provides a comprehensive description of health literacy ( 14 ). So far there are only a few studies which applied a selection of two ( 15 ) or four domains ( 16 , 17 ) of the HLQ, and only two studies used all nine domains ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies found that hospital readmissions within a month of PCI are 75% higher amongst patients with limited H.L. [42,43]. Numerous studies suggest that hospitalbased and pre-discharge educational strategies improve treatment outcomes and reduce atherosclerosis recurrence, resulting in CHD [44][45][46].…”
Section: Introductionmentioning
confidence: 99%